Perforation of polycarbonate sheet when subjected to impact test– A review - Hasan, Muhamad Abid; H. Shah, Qassim; Shaik Dawood, Mohd. Sultan Ibrahim (Research India Publications, 2017)
Polycarbonate (PC) material has a variety of applications which offers high resistance to impact loadings. Perforation performance of a projectile striking a PC target is the main character that determines the resistance capability of PC mate-rial. There are three methods to investigate the PC penetration trajectories such as experimental test, numerical modeling and combination of experimental and simulation values. The ob-jective of this review paper is to discuss all the available re-search methods on the penetration of PC material, and record their potential and lack areas. Moreover investigations of mul-tilayered plates with different materials bonded together with PC plates to observe the impact effects of different projectiles shapes are been discussed. Furthermore the analysis of PC material behaviors during different stress-strain rates are also been presented in this paper.